Emotional Intelligence: A Novel Outcome Associated with Wellbeing and Self-Management in Chronic Obstructive Pulmonary Disease - Benzo, Roberto P. (Ann Am Thorac Soc, 2016)
Rationale: Individuals with chronic obstructive pulmonary disease (COPD) often struggle with diminished autonomy and quality of life. Emotional factors play a crucial role in the well-being of patients with COPD; they are independently associated with critical outcomes such as dyspnea, quality of life, and health care use. Emotional intelligence is the capacity to understand and manage personal thoughts and feelings, as well as to positively influence interpersonal communication and social well-being. Emotional intelligence is a trainable skill that is extensively used in corporate business to improve well-being and performance, and it may also be significant in the self-management of emotions in patients with chronic disease. Importantly, research supports the proposition that emotional intelligence may be developed and learned at any time or any age, and training programs have been associated with increased well-being and better emotional regulation in patients with chronic disease. However, to date, no research has been done to investigate its value in patients with COPD. Objectives: We aimed to investigate the association between emotional intelligence and two meaningful outcomes in COPD: quality of life and self-management abilities. Methods: Participants with moderate to severe COPD completed a disease-specific quality of life tool (Chronic Respiratory Questionnaire), the Trait Emotional Intelligence Questionnaire, the Self-Management Abilities Scale, the modified Medical Research Council Dyspnea Scale, and pulmonary function tests, and also provided information about living conditions and self-reported health care use. Measurements and Main Results: A total of 310 patients with COPD (mean age, 69 ± 9 yr; 40% female; mean FEV(1)%, 42.4 ± 15.8) participated in the study. Emotional intelligence was significantly and independently associated with self-management abilities (P < 0.0001) and all domains of quality of life assessed (dyspnea, fatigue, emotions, and mastery; P < 0.0001) after adjusting for age, degree of bronchial obstruction, breathlessness, and other significant confounders. Conclusions: Emotional intelligence may represent an important attribute in COPD, as it is associated with self-management abilities and all domains of quality of life, regardless of age or disease severity. Emotional intelligence can be learned and may complement existing rehabilitation efforts. Attention to it may address the current gap that exists in the treatment of emotional components of COPD responsible for decreased quality of life and increased health care use.